2022
DOI: 10.3390/biomedicines10123276
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Disassembly: What Can We Learn from Chaperones?

Abstract: Protein aggregation and subsequent accumulation of insoluble amyloid fibrils with cross-β structure is an intrinsic characteristic of amyloid diseases, i.e., amyloidoses. Amyloid formation involves a series of on-pathway and off-pathway protein aggregation events, leading to mature insoluble fibrils that eventually accumulate in multiple tissues. In this cascade of events, soluble oligomeric species are formed, which are among the most cytotoxic molecular entities along the amyloid cascade. The direct or indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 219 publications
(294 reference statements)
0
9
0
Order By: Relevance
“…We found that the formation of Aβ42 fibrils was attenuated by astemizole, which was in line with a previous study that used a radioligand assay [ 15 ], but astemizole did not prevent the amyloid assembly of α-syn, even at a high molar ratio. Our results suggest that the ameliorative effects of astemizole on the formation of amyloids are rather protein-specific, while previously reported small-molecule inhibitors or chaperones can inhibit the formation of a range of amyloid proteins [ 26 , 27 ]. For example, epigallocathecin-3-gallate and several polyphenol molecules inhibit the aggregation of Aβ, α-syn, tau, human islet amyloid polypeptide, and the prion protein Sup35 [ 26 ].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…We found that the formation of Aβ42 fibrils was attenuated by astemizole, which was in line with a previous study that used a radioligand assay [ 15 ], but astemizole did not prevent the amyloid assembly of α-syn, even at a high molar ratio. Our results suggest that the ameliorative effects of astemizole on the formation of amyloids are rather protein-specific, while previously reported small-molecule inhibitors or chaperones can inhibit the formation of a range of amyloid proteins [ 26 , 27 ]. For example, epigallocathecin-3-gallate and several polyphenol molecules inhibit the aggregation of Aβ, α-syn, tau, human islet amyloid polypeptide, and the prion protein Sup35 [ 26 ].…”
Section: Discussionmentioning
confidence: 49%
“…For example, epigallocathecin-3-gallate and several polyphenol molecules inhibit the aggregation of Aβ, α-syn, tau, human islet amyloid polypeptide, and the prion protein Sup35 [ 26 ]. Molecular chaperones including intracellular heat-shock proteins have anti-amyloid activities on α-syn, Aβ42, tau, and SOD1 proteins [ 27 , 28 , 29 ]. The observed target-amyloid selectivity of astemizole is not unprecedented; a previous study showed that astemizole displayed different affinities for Aβ42 and tau aggregates [ 15 ], and further studies are needed to determine the reasons for the proposed selectivity of astemizole.…”
Section: Discussionmentioning
confidence: 99%
“…Desaggregases are being intensively investigated as potential drugs targeting protein misfolding and aggregation [40,41]. Agents able to disaggregate preformed amyloids have been classified as molecular chaperones (e.g., Hsp70 and Hsp90), chemical chaperones (bile acids, steroid hormones, and trehalose) and pharmacological chaperones (amino acid derivatives, benzophenone, and tetracycline) [42]. The bacterial ATPases of the Clp proteins family have been suggested to be used for such purposes [43].…”
Section: Discussionmentioning
confidence: 99%
“…Catechin derivatives, non-steroidal anti-inflammatory drugs (NSAIDs), anthracycline, and tetracycline derivatives also show the ability to disassemble protein aggregate. However, they still need more research to clarify the mechanism and reveal potential risks before use in clinical treatment [100][101][102][103].…”
Section: The Way To Eliminate Protein Aggregatesmentioning
confidence: 99%